Piloting a systems level intervention to improve cervical cancer screening, treatment and follow up in Kenya - Mabachi, Natabhona M.; Wexler, Catherine; Acharya, Harshdeep; Maloba, May; Oyowe, Kevin; Goggin, Kathy; Finocchario-Kessler, Sarah (Frontiers in Medicine, 2022)
Although preventable, Cervical Cancer (CC) is the leading cause of cancer deaths among women in Sub-Saharan Africa with the highest incidence in East Africa. Kenyan guidelines recommend an immediate screen and treat approach using either Pap smear or visual screening methods. However, system (e.g., inadequate infrastructure, weak treatment, referral and tracking systems) and patient (e.g., stigma, limited accessibility, finance) barriers to comprehensive country wide screening continue to exist creating gaps in the pathways of care. These gaps result in low rates of eligible women being screened for cervical cancer and a high loss to follow up rate for treatment. The long-term goal of 70% CC screening and treatment coverage can partly be achieved by leveraging mHealth tools to support service efficiency and client retention. To help address system level barriers to CC screening treatment and follow up, our team developed an mHealth tool - the Cancer Tracking System (CATSystem), to support cervical cancer screening, treatment, and on-site and external referrals for reproductive age women in Kenya. Preliminary data showed a higher proportion of women enrolled in the CATSystem receiving clinically adequate (patients tested positive were treated or rescreened to confirm negative within three months) follow up after a positive/suspicious screening, compared to women in the retrospective arm.